Green and Low-Cost Membrane Electrode Assembly for Proton Exchange Membrane Fuel Cells: Effect of Double-Layer Electrodes and Gas Diffusion Layer - Gouda, M. H.; Elnouby, Mohamed; Aziz, Andrew N.; Youssef, M. Elsayed; Santos, D. M. F.; Elessawy, Noha A. (Frontiers in Materials, 2020)
The success of fuel cells depends on the design structure meanwhile catalysts electrodes and membrane allowing easy access of oxygen and protons. Using non-precious catalyst electrodes based on recyclable carbon nanostructures is most important to produce clean energy and increase the ability to commercialize the fuel cells. Herein, reduced graphene oxide (rGO) and graphene/magnetic iron oxide nanocomposite (rGO/MIO) are successfully synthesized as anode and cathode respectively from polyethylene terephthalate (PET) waste bottles using easy steps in order to simplify the method and reducing the production cost. While, the membrane is prepared from low cost and eco-friendly ternary polymers blend which are polyvinyl alcohol (PVA), polyethylene oxide (PEO) and polyvinyl pyrrolidone (PVP) then doped with sulfonated graphene oxide. The prepared electrodes have characteristic high porosity and their electrocatalytic performances are evaluated using three-electrode cell electrochemical studies as cyclic voltammetry and linear scan voltammetry combined with rotating disk electrode. A new assembly of the membrane between two non-precious catalyst electrodes as a single polymer electrolyte membrane fuel cell (PEMFC) was developed using a catalyst-coated membrane technique. The membrane electrode assembly (MEA) design parameters which affect its performance in hydrogen fuel cells as number of used catalyst layers (CL) or using gas diffusion layer (GDL) were evaluated in a single cell set-up with H2/O2 operation and the results revealed that the performance MEA was enhanced with using GDL more than that of MEA without GDL by 66% at a current density of 0.8 A cm−2 while the performance with double CL was better than that of the conventional single CL by 30 % at a current density of 0.98 mA cm−2.